MOTIVASI KERJA DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA DI KABUPATEN BONE BOLANGO - Sri Nining Suhasti Mopangga; Usman Moonti; Rusli Isa (Universitas Bina Taruna Gorontalo, 2023)
ABSTRACT The purpose of this research was to find out whether there is an influence of work motivation on the performance of employees at the Community and Village Empowerment Office in Bone Bolango Regency. This research used a quantitative approach, with the Ex-post facto research method. The data used were primary data obtained from Distributing questionnaires to Community and Village Empowerment Office Employees in Bone Bolango Regency. The number of samples in this study was 31 respondents. The data analysis technique used was simple linear regression. The results of the study showed that there is an influence of work motivation on the performance of employees at the Community and Village Empowerment Office in Bone Bolango Regency. The magnitude of the influence of work motivation was 39,5% while the remaining 60,5% was influenced by variables that were not examined.